Revision of the bryozoan genus Gephyrotes Norman, 1903 (Cheilostomata, Cribrilinidae) with the description of two new taxa - Martino, Emanuela Di; Rosso, Antonietta (Zootaxa, 2015)
The finding of a new species of Gephyrotes, G. moissettei n. sp., in Miocene deposits of southern Italy, prompted a revision of this distinctive cribrimorph taxon, leading to the redescription and first SEM documentation of the type material of nine species. Five of them are retained in Gephyrotes, namely the type species, G. nitidopunctatus, and G. fortunensis, G. spectabilis, G. quadriserialis, and G. convexus, to which G. moissettei n. sp. is added. The only Recent species is the genotype, while all the others are fossils from North America, Europe and northwest Africa. Two further species are transferred to the genus Tricephalopora, namely T. saillans and T. levigata, whereas Spiniflabellum n. gen., is established to accommodate a species from the Caribbean area, S. spinosum, previously assigned to Gephyrotes.